Kidney injury molecule type-1, interleukin-18, and insulin-like growth factor binding protein 7 levels in urine to predict acute kidney injury in pediatric sepsis - Ganda, Idham Jaya; Kasri, Yusriwanti; Susanti, Maya; Hamzah, Fitrayani; Rauf, Syarifuddin; Albar, Husein; Aras, Jusli; Fikri, Bahrul; Lawang, Sitti Aizah; Daud, Dasril; Laompo, Amiruddin; Massi, Muhammad Nasrum (Frontiers in Pediatrics, 2022)
Background: This study aimed to observe the role of urinary KIM-1, IL-18, and IGFBP-7 levels in predicting AKI in chil-dren with sepsis. Material and Methods: This prospective cohort observational study was conducted at Dr. RSUP. Wahidin Sudirohuso-do, Makassar, South Sulawesi from January to December 2021. Inclusion criteria were Septic patients treated in the PICU aged 1 month to 18 years with normal serum creatinine or normal urine output (>5 ml/kg/BW/hour in 6-12 hours). Pa-tients with a history of kidney disease, a prior urinary tract infection, or a history of using nephrotoxic drugs were ex-cluded. Results: There was a significant difference in urinary KIM-1, IL-18, and IGFBP-7 levels between septic patients with AKI and without AKI. The cut-off point for urinary KIM-1 level in sepsis with AKI and without AKI was 1.666 ng/ml, with sensitivity of 82.5%, specificity of 82.2%, and a relative risk (RR) of 95% confidence interval (CI) of 6.866 (3.329–14.165). The cut-off point for urinary IL-18 levels was 3.868 ng/ml, with sensitivity of 92.50%, specificity of 91.78%, and RR of (95%CI) 20.078 (6.593-61.142). The cut-off point for urinary IGFBP-7 levels was 0.906 ng/ml with a sensitivity 75.00%, specificity 75.34%, RR (95% CI) 4.063 (2.206-7.483). Conclusion: Urinary levels of KIM-1, IL-8, and IGFBP-7 might be used as predictor of AKI in Septic patients. Urinary IL-8 has higher sensitivity and specificity as a predictor for AKI in sepsis patients.